Searching For Tax Revenue Determinants in N-11: The Moderating Role of Regulatory Quality - Emilio Pascal; Suparna Wijaya (Ilomata International Journal of Tax and Accounting, 2023)
This study aimed to analyze the effects of the agricultural sector and the Foreign Direct Investment (hereinafter referred to as FDI) on tax revenue in The Next Eleven (N-11) countries. In this research, a moderating variable of regulatory quality was used. The data were obtained from the World Bank and analyzed using panel data regression. The dependent variable in this study was tax revenue, whereas the independent variables comprised the agricultural sector, the FDI, the agricultural sector moderated by regulatory quality, the FDI moderated by regulatory quality, and the regulatory quality. The results indicate that all independent variables simultaneously affect tax revenue. However, when investigating partially, FDI, the agricultural sector moderated by regulatory quality, and regulatory quality have a positive effect on tax revenue while FDI moderated by regulatory quality shows a negative effect on tax revenue. As for the agricultural variable, a significant effect on tax revenue was not shown. It is recommended that governments in N-11 countries focus on developing quality regulations in another sector, particularly agriculture, and encourage foreign investments since these two aspects are proven to increase tax revenue.